2018
DOI: 10.5539/ijbm.v13n4p138
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of IFRS Adoption on the Value Relevance of Accounting Information: Evidence from the Insurance Sector

Abstract: This paper aims to investigate whether the adoption of International Financial Reporting Standards (IFRS) increases the value relevance of accounting information for insurance firms listed in the Saudi stock market. The study employs the Ohlson model (1995) and the Easton-Harris valuation model (1991) in order to examine the association among stock market value and book value and earnings per share. The data was collected for 21 insurance companies listed in the Saudi stock market during the period 2007-2014, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 30 publications
4
29
1
Order By: Relevance
“…Oraby’s (2017) study examines Saudi financial sector companies and finds that the adjusted R 2 of earnings is higher than BVE when decomposing models are used for the comparison. Another study by Alnodel (2018) found that the change in value relevance of the selected sample was not due to IFRS adoption, but rather to firm factors such as size and profitability. A more recent study by Ebaid (2021) reported that the quality of financial information has improved since Saudi adoption of IFRS.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Oraby’s (2017) study examines Saudi financial sector companies and finds that the adjusted R 2 of earnings is higher than BVE when decomposing models are used for the comparison. Another study by Alnodel (2018) found that the change in value relevance of the selected sample was not due to IFRS adoption, but rather to firm factors such as size and profitability. A more recent study by Ebaid (2021) reported that the quality of financial information has improved since Saudi adoption of IFRS.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…A review of prior relevant literature shows several limitations in conducting the analysis of value relevance research: for example, improper implementation of models (Belassi and Elbarrad, 2020), neglecting the use of a deflator (Alnodel, 2018), using a multi‐country comparison by overlooking the country‐specific context (El‐Diftar and Elkalla, 2019), using a small sample size (Oraby, 2017), ignoring the use of valuation models (Ebaid, 2021) or failing to use the R 2 comparison tests (Oraby, 2017; Alnodel, 2018). Therefore, a more refined research design is necessary to provide more valid results on the impact of IFRS adoption on the value relevance of accounting information of listed firms on the Saudi stock market.…”
Section: Introductionmentioning
confidence: 99%
“…Hifza [18] stated that profitability is one of the important aims of financial management since the prime aim of the financial investment is to maximize the owners' wealth and profitability is very germane as a determinant of business investment success and financial performance. The market share price of companies depends fundamentally on the ability of the company to make a profit on a continuous basis and ensure that the going concern principle is not being threatened [19].…”
Section: Firm Performancementioning
confidence: 99%
“…In this regard, Polonchek and Miller (1999) argue that, historically, investors of insurance companies were relatively uninformed, "since the perceived risk of holding insurance company securities was low and the perceived quality of insurance company assets was high" (Polonchek & Miller, 1999, p. 459). However, these perceptions changed through time, especially after the 90's and the 2008's subprime financial crisis, since most of the assets and liabilities of insurance companies are measured at the fair value and potentially affected by managers' judgment and subjectivism (Alnodel, 2018), making the accounting process a key element for decision-making by investors and regulators.…”
Section: Introduction Introductionmentioning
confidence: 99%